Receptivity of providing firearm safety storage devices to parents along with firearms safety education - Fraser Doh, Kiesha; Bishop, Zhana; Gillings, Trishanne; Johnson, Jonathan; Boy, Angela; Waris, Rabbia S.; Bhatia, Amina M.; Santore, Matthew T.; Simon, Harold K. (Frontiers in Public Health, 2024)
Background In the United States, 33% of households with children contain firearms, however only one-third reportedly store firearms securely. It’s estimated that 31% of unintentional firearm injury deaths can be prevented with safety devices. Our objective was to distribute safe storage devices, provide safe storage education, evaluate receptivity, and assess impact of intervention at follow-up. Method At five independent, community safety events, parents received a safe storage device after completing a survey that assessed firearms storage methods and parental comfort with discussions regarding firearm safety. Follow-up surveys collected 4 weeks later. Data were evaluated using descriptive analysis. Result 320 participants completed the surveys, and 288 participants were gunowners living with children. Most participants were comfortable discussing safe storage with healthcare providers and were willing to talk with friends about firearm safety. 54% reported inquiring about firearm storage in homes their children visit, 39% stored all their firearms locked-up and unloaded, 32% stored firearms/ammunition separately. 121 (37%0.8) of participants completed the follow-up survey, 84% reported using the distributed safety device and 23% had purchased additional locks for other firearms. Conclusion Participants were receptive to firearm safe storage education by a healthcare provider and distribution of a safe storage device. Our follow up survey results showed that pairing firearm safety education with device distribution increased overall use of safe storage devices which in turn has the potential to reduce the incidence of unintentional and intentional self-inflicted firearm injuries. Providing messaging to promote utilization of safe storage will impact a firearm safety culture change.